2001
DOI: 10.1002/1521-3803(20010801)45:4<241::aid-food241>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, nutritional and sensory properties of bread supplemented with lupin seed (Lupinus albus) products

Abstract: Sweet lupin Lupinus albus seed flour (SLSF), two sweet lupin protein isolates (SLPI-I and SLPI-II) and sweet lupin seed protein concentrate (SLSPC) were added to wheat flour (WF) in an amount of 3, 6, 9 and 12% of wheat flour. The effects of lupin products supplementation on physical dough properties were studied using a Brabender farinograph. Loaves were prepared from the various blends using the straight dough procedure and then evaluated for volume, crust and crumb colour, crumb texture, flavour and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
7
36
0
2
Order By: Relevance
“…The slight loss of volume observed for blends of wheat and lupine has also been seen in previously published studies and was attributed to a decrease in the content or quality of gluten (Campos and ElDash, 1978;Ballester et al, 1984;Dervas et al, 1999;Mubarak, 2001;Doxastakis et al, 2002). In the present study, the crusts of the breads made with lupine flour showed small pores, probably because the mesh that forms the gluten around the starch granules was weaker than in whole wheat bread.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The slight loss of volume observed for blends of wheat and lupine has also been seen in previously published studies and was attributed to a decrease in the content or quality of gluten (Campos and ElDash, 1978;Ballester et al, 1984;Dervas et al, 1999;Mubarak, 2001;Doxastakis et al, 2002). In the present study, the crusts of the breads made with lupine flour showed small pores, probably because the mesh that forms the gluten around the starch granules was weaker than in whole wheat bread.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with those obtained by Campos and El-Dash (1978), which showed that the addition of up to 10% of lupine had no negative effect on the smell or the flavour of the bread. In contrast, there was a significant loss of texture and flavour of the bread when using more than 6% of lupine flour in the study by Mubarak (2001).…”
Section: Breadmentioning
confidence: 60%
See 2 more Smart Citations
“…Th e defatted flour could substitute 10 % of wh eat flour and produce an acceptable bread quality (Dervas et al , 1999). Substitution of wheat flour with up to 6 % of lupin flour had no detrimental effect on sensory properties of the bread (Mubarak, 2001). White lupin f lour can substitu te wheat flour at levels up to 5 % for baking white 'wheat' bread and has a greater potential for substitution of wheat flour than fl our from narrow-leaved lupin.…”
Section: Exposure 41 Use Of Flourmentioning
confidence: 97%